Efektivitas Pijat Endorphin Dengan Pijat Oksitosin Terhadap Penurunan Nyeri Persalinan Kala I - Aritonang, Tetty Rina; Pangaribuan, Maslan; Riyadi, Sabrina; Soleha, Siti; Sari, Fatmah; Dahliah, Dahliah; Lianti, Nadia Rizky; Anggraini, Tiara; Rahmawati, Dewi (NHM PRESS, 2023)
Background: Labor pain is a normal condition experienced by mothers before giving birth, which can cause discomfort caused by stimulation of certain nerve endings. One way to reduce labor pain is to use non-pharmacological methods, namely giving endorphin and oxytocin massage. Childbirth is the process in which the products of conception such as the fetus, placenta and amniotic fluid are expelled, whether at term or preterm, either through the birth canal or another way and is marked by the opening and thinning of the cervix. Purpose: To determine the effect of endorphin massage with oxytocin on reducing pain in mothers during childbirth. Method: Examining articles published via the Google Scholar site from 14 journals. Results: Based on this system, it can be concluded that there is an effect on reducing the intensity of labor pain during the first active phase in mothers giving birth.